Option Pricing of an Asset with Seasonal and Periodic Supply - Rangita, Apaka; Onyango, Silas N.; Ongati, Omolo; Nyakinda, Otula (International Journal of Multidisciplinary Sciences and Engineering, 2014)
In option pricing the rate of change of asset price with time can be viewed to be directly proportional to the Walrasian [6] excess demand. Scholars such as Jacques [3] and Onyango [4], have used the excess demand concept with linearised demand and supply functions to derive and solve both deterministic and stochastic logistic differential equations for stock price. The underlying assets in option pricing are unique and can be seasonal and periodic like for electricity, water and other ‘weather’ derivatives. In this paper we develop and solve both deterministic and stochastic logistic differential equations for option pricing using the excess demand concept but with a linear demand function and a seasonal and periodic supply function.
Keywords: Supply; Demand; Equilibrium; Deterministic; Stochastic; Logistic; Differential Equations